Diagnosis of Lyme-associated uveitis: value of serological testing in a tertiary centre. Issue 3 (28th June 2017) - Bernard, Alexia; Kodjikian, Laurent; Abukhashabh, Amro; Roure-Sobas, Chantal; Boibieux, Andre; Denis, Philippe; Broussolle, Christiane; Seve, Pascal
Abstract : Aims: To determine the frequency and clinical presentation of Lyme disease in patients with uveitis and to assess the value of Borrelia burgdorferi serological testing. Methods: Retrospective study on all patients with uveitis who were referred to our tertiary hospital were serologically tested for Lyme in our laboratory between 2003 and 2016. Screening consisted of determining B. burgdorferi serum IgG and IgM by ELISA method. The patient's serology was considered as positive if the ELISA-positive result in IgM and/or IgG was confirmed by an immunoblot positive in IgM and/or IgG. Lyme-associated uveitis was diagnosed based on serological results as well as response to antibiotics and exclusion of other diagnosis. Results: Of the 430 patients with uveitis (60% women, mean age 49 years) fulfilling inclusion criteria, 63 (14.7%) had an ELISA-positive serology, confirmed by immunoblot for 34 patients (7.9%). The diagnosis of Lyme-associated uveitis was finally retained in seven patients (1.6%). These patients reported either a previous exposure including tick bite or forest walks (n=5), symptoms suggestive of Lyme disease (n=5) and resistance to local and/or systemic steroids (n=7). Among the remaining 27 positive patients, 22 had other established aetiologies and 5 other were unclassified. Conclusion: The seroprevalence of B. burgdorferi among our patients with uveitis was 7.9% compared with 6 to 8.5% in the general French population which leads to a low predictive value of serological testing. Its use should be reserved for patients with unexplained uveitis, an exposure history, systemic findings suggestive of Lyme disease and steroids resistance.